Contextual factors and clinical reasoning: differences in diagnostic and therapeutic reasoning in board certified versus resident physicians - Elexis McBee; Temple Ratcliffe; Katherine Picho; Lambert Schuwirth; Anthony R. Artino; Ana Monica Yepes-Rios; Jennifer Masel; Cees van der Vleuten; Steven J. Durning (BMC Medical Education, 2017)
Abstract Background The impact of context on the complex process of clinical reasoning is not well understood. Using situated cognition as the theoretical framework and videos to provide the same contextual “stimulus” to all participants, we examined the relationship between specific contextual factors on diagnostic and therapeutic reasoning accuracy in board certified internists versus resident physicians. Methods Each participant viewed three videotaped clinical encounters portraying common diagnoses in internal medicine. We explicitly modified the context to assess its impact on performance (patient and physician contextual factors). Patient contextual factors, including English as a second language and emotional volatility, were portrayed in the videos. Physician participant contextual factors were self-rated sleepiness and burnout.. The accuracy of diagnostic and therapeutic reasoning was compared with covariates using Fisher Exact, Mann-Whitney U tests and Spearman Rho’s correlations as appropriate. Results Fifteen board certified internists and 10 resident physicians participated from 2013 to 2014. Accuracy of diagnostic and therapeutic reasoning did not differ between groups despite residents reporting significantly higher rates of sleepiness (mean rank 20.45 vs 8.03, U = 0.5, p < .001) and burnout (mean rank 20.50 vs 8.00, U = 0.0, p < .001). Accuracy of diagnosis and treatment were uncorrelated (r = 0.17, p = .65). In both groups, the proportion scoring correct responses for treatment was higher than the proportion scoring correct responses for diagnosis. Conclusions This study underscores that specific contextual factors appear to impact clinical reasoning performance. Further, the processes of diagnostic and therapeutic reasoning, although related, may not be interchangeable. This raises important questions about the impact that contextual factors have on clinical reasoning and provides insight into how clinical reasoning processes in more authentic settings may be explained by situated cognition theory.